A critical review of the impacts of split injection strategies on the performance, combustion and emissions characteristics of a diesel engine fueled with low carbon alcohol fuels. (2023) - Shekar Kuppili, Yuvaraj; Kumar, Prem; Singh Sandhu, Sarbjot
Abstract: This paper reviews the impacts of split (pilot/main) injection tactics on the exhaust pollutants, performance, and combustion of compression ignition (CI) engines operated with low carbon alcohols fuels. For the past several years, scholars have been attempting to simultaneously reduce NOx and soot emissions by enhancing combustion, which is accomplished by optimizing the fuel injection technique by using high amount of EGR or low carbon alcohols fuels. Split injection tactics are used in the diesel engines to accomplish the partially premixed combustion (PPC). The prolonged ignition delay (ID) in PPCI engines improves air/fuel mixing, resulting in lower soot and NOx emissions. Furthermore, due to the more substantial charge cooling effect of low carbon alcohol fuels reduce the combustion temperature, resulting in lower NOX emissions. Thus, combining a split injection approach with low-carbon alcohol fuels in a modern CI engine might be a promising option to satisfy stringent exhaust pollution regulations as well as reducing dependency on fossil fuels. The present paper focuses on the work done in the area of split injection strategies with various low-carbon alcohol fuels and the effects of injection pressures on engine performance.